Swine Manure Composting With Compound Microbial Inoculants: Removal of Antibiotic Resistance Genes and Their Associations With Microbial Community - Li, Ke; Cao, Rui; Mo, Shangkun; Yao, Rensheng; Ren, Zhuqing; Wu, Jian (Frontiers in Microbiology, 2020)
In this study, compound microbial inoculants, including three Bacillus strains and one Yeast strain, were inoculated into swine manure composting to explore the effects on antibiotic resistance genes (ARGs) and Mobile genetic elements (MGEs), microbial community structure and pathogenic bacteria. The results indicated that the abundances of the detected ARGs ranged from 3.6×103 to 1.13×108 copies/g. The ARGs with the highest abundance was sul2, and the lowest was blaCTX. Composting removes most of ARGs and MGEs by 22.8%-99.7%. These ARGs were significantly reduced during the thermophilic phase of compost. The removal rate of ARGs at the different layer of compost pile was different as follows: middle layer > upper layer > lower layer. But some ARGs proliferated significantly in the maturation phase of compost, especially the sulfonamide resistance genes. Compound microbial inoculants increased the temperature of compost, accelerated water loss, nitrogen fixation and increased the removal rate of β-lactamase resistance genes, the transposon gene tn916 and part of tetracycline resistance genes by 3.7%-23.8% in compost. Compound microbial inoculants changed the community structure and increased the Bacillus abundance in the thermophilic phase of compost. And it was helpful for removing pathogens during composting. The addition of compound microbial inoculants causes the decrease of Firmicutes and the increase of Bacteroidetes, which may be related to the removal and proliferation of ARGs.